Histone Deacetylase-1 (HDAC1) Is a Molecular Switch between Neuronal Survival and Death - Bardai, Farah H. (American Society for Biochemistry and Molecular Biology, 2012)

(untitled)
Both neuroprotective and neurotoxic roles have previously been described for histone deacetylase-1 (HDAC1). Here we report that HDAC1 expression is elevated in vulnerable brain regions of two mouse models of neurodegeneration, the R6/2 model of Huntington disease and the Ca(2+)/calmodulin-dependent protein kinase (CaMK)/p25 double-transgenic model of tauopathic degeneration, suggesting a role in promoting neuronal death. Indeed, elevating HDAC1 expression by ectopic expression promotes the death of otherwise healthy cerebellar granule neurons and cortical neurons in culture. The neurotoxic effect of HDAC1 requires interaction and cooperation with HDAC3, which has previously been shown to selectively induce the death of neurons. HDAC1-HDAC3 interaction is greatly elevated under conditions of neurodegeneration both in vitro and in vivo. Furthermore, the knockdown of HDAC3 suppresses HDAC1-induced neurotoxicity, and the knockdown of HDAC1 suppresses HDAC3 neurotoxicity. As described previously for HDAC3, the neurotoxic effect of HDAC1 is inhibited by treatment with IGF-1, the expression of Akt, or the inhibition of glycogen synthase kinase 3β (GSK3β). In addition to HDAC3, HDAC1 has been shown to interact with histone deacetylase-related protein (HDRP), a truncated form of HDAC9, whose expression is down-regulated during neuronal death. In contrast to HDAC3, the interaction between HDRP and HDAC1 protects neurons from death, an effect involving acquisition of the deacetylase activity of HDAC1 by HDRP. We find that elevated HDRP inhibits HDAC1-HDAC3 interaction and prevents the neurotoxic effect of either of these two proteins. Together, our results suggest that HDAC1 is a molecular switch between neuronal survival and death. Its interaction with HDRP promotes neuronal survival, whereas interaction with HDAC3 results in neuronal death.